Análise dos livros didáticos de língua portuguesa sob a perspectiva da sociolinguística educacional - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This work was developed within the scope of the Postgraduate Program in Teaching Sciences and Humanities - PPGECH, whose general objective was to carry out an analysis of the Portuguese Language Didactic Books from the perspective of Educational Sociolinguistics, in order to contribute to the reflection on the conceptions of language, language and grammar and their influence on Portuguese Language teaching in the context of High School. This research was of a theoretical nature, in which the corpus was constituted by seven (7) books referring to the 1st year of High School, approved by the National Program of the Didactic Book for the triennium (2018-2020), and developed from the qualitative approach which considered Textual Analysis, Thematic Analysis and Interpretive Analysis, based on Severino (2002), and Bardin's Content Analysis (1977). For the analysis of the data the following questions were considered: a) Did the textbooks present the most monitored or more colloquial of the language and the linguistic adequacy? b) The books present the socio-symbolic values as the notion of "right" and "wrong"; standard-norm, culture-norm, linguistic prejudice, linguistic variation and linguistic change? c) Do books present aspects of oral and written? and; d) Do the linguistic knowledge presented in the textbooks lead to a reflection on language, language and grammar? In order to base this study and answer such questions it was considered: Bortoni-Ricardo (2005) author of the theory of Educational Sociolinguistics; the National Curricular Parameters (PCNs); the Curricular Parameters for High School (PCNEM); the National Curricular Guidelines for Secondary Education (OCEM); the new National Common Curricular Base for High School (BNCC) and other authors that discuss the sociolinguistic aspects in the school context, as well as Bagno (2015, 2014, 2012, 2007, 2006, 2003, 1999); Coelho (2007); Cyranka (2011); Dias (2011); Faraco (2016, 2015); Geraldi (2015, 1984); Marscuschi (2010, 2008); Mendonça (2006); Possenti (1996), Rojo (2006), Tarallo (1988) and Travaglia (2009, 1996). Thus, the data showed that textbooks, although they do not explicitly adopt the theory of educational sociolinguistics, implicitly carry their assumptions, since they adopt the conceptions of a Portuguese language teaching that considers the linguistic knowledge that the student holds and its social and cultural context. It also presents the teacher as the mediator of knowledge, who reflects on the language, language and grammar and leads the students to a knowledge and / or amplification of their linguistic repertoire that allows them to cross between the various styles and different communicative situations found in the society, thus contributing to the "culturally sensitive pedagogy" of Bortoni-Ricardo (2005).
Keywords: Sociolinguística educacional; Livros didáticos; Ensino médio; Língua portuguesa; Gramática; Educational Sociolinguistics; Didactic books; High school; Portuguese; Grammar; CIENCIAS HUMANAS: EDUCACAO